Control rod position measurement by two-electrode capacitance sensor in nuclear heating reactor. Issue 1 (2nd January 2019) - Hu, Guang; Qin, Benke; Liu, Qianfeng; Bo, Hanliang
ABSTRACT: This study employed a new method for measuring the ungrounded/grounded control rod position. In this connection, a sensor system based on the two-electrode capacitance is applied to measure the rod position in NHR. The application of the capacitance sensor is extensively developed with measuring insulating objects. However, the capacitance sensors measuring for ungrounded/grounded control rod position are seldom studied earlier. In addition, the proposed model was set up with ungrounded/grounded control rod for the two-electrode sensor. According to the different electric properties of ungrounded and grounded control rod, this apparatus determines the control rod position using an interface electronics method and two-electrode capacitance sensor. The subsequent experiment and calibration analyses on the data indicate the high reliability and accuracy of the apparatus for monitoring rod position. It is demonstrated that such a system can be applied to automatic real-time monitoring of control rod positon in nuclear heating reactor.